Focal hepatic uptake along the falciform: False positive for malignancy on 18F-FDG-PET in a lymphoma patient with superior vena cava obstruction - Sarah Carpenter, MD; Jennifer Tomich, MD; Daniel Young, MS; Lester Johnson, MD, PhD (Radiology Case Reports, 2014)
We present a case of focal increased intrahepatic radiotracer activity on 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) in a patient with lymphoma and superior vena cava (SVC) obstruction, a false positive for malignancy. Contrast-enhanced computed tomography (CT) demonstrated an enhancing region of geographic focal hypoattenuation in the liver along the falciform, corresponding to the region of increased radiotracer activity on FDG-PET, with marked narrowing of the superior vena cava and resultant collateral venous pathways to the portal vein via paraumbilical veins. CT followup demonstrated stability of the hepatic abnormality, and no lesion was evident on ultrasound, suggesting that the finding on PET-CT represented a false positive for malignancy in this patient with known SVC obstruction. In patients with SVC obstruction, radiologists should consider this phenomenon of anomalous hepatic uptake along the falciform as a source of possible false positives for malignancy on PET.